POSITIVE ELECTRODE FOR LITHIUM ION CAPACITOR, AND LITHIUM ION CAPACITOR - YAMAMOTO, Norihiro; KOJIMA, Kenji (2018)
An object of the present invention is to provide a positive electrode for a lithium ion capacitor capable of suppressing an increase in resistance at low temperatures and improving initial discharge capacity and energy density at low temperatures, thereby reducing a lowering rate of charge and discharge capacity at -30°C with respect to that at normal temperature, and a lithium ion capacitor using the positive electrode. The positive electrode of the present invention includes a positive electrode layer (A) which, after a following pretreatment for measurement, has a volume of pores having a pore size of not lower than 1.0 nm and lower than 1.4 nm of not lower than 0.11 cc/g, the pore size being calculated by an HK method, and a total pore volume calculated by a BET method of not more than 1.1 cc/g. Pretreatment for measurement: the positive electrode is taken out of a cell having a cell voltage of 3 V, cut out and immersed in 10 cc of dehydrated acetonitrile per 1 cm 3 of the positive electrode at 25°C for 10 minutes with stirring. This immersion is repeated three times and the positive electrode is subjected to a pre-drying treatment at 60°C for 1 hour. The positive electrode layer (A) is scraped off from the positive electrode obtained by the pre-drying treatment and dried for 2 hours under conditions of 200°C and a pressure reduced to 5.5 Pa.